The Relationship Between Leg Length, Leg Muscle Explosive Power and The Ability To Run 100 Meter Sprint For Male Students In Class X At SMAN 2 Seluma - Alexon Alexon; Santun Sihombing; Wiwik Yunitaningrum; Julio Dwi Putra (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the relationship between limb length, leg muscle explosive power and the ability to run 100 meters sprint in male students of class X in SMAN 2 Seluma. This type of research is multiple correlation research. The population in this study were the sons of class X at SMAN 2 Seluma totaling 65 students. sampling technique is purposive sampling the number of samples is 40 people. The instruments used were leg length measurement, vertical jump  test and sprint 100 meterFrom the calculation results, the conclusion in this study is that there is a very strong relationship between leg length and the ability to run sprint 100 meterThere is a very strong relationship between leg muscle explosive power and the ability to run sprint 100 metersthere is a very strong relationship between leg length, leg muscle explosive power and the ability to run sprint in male students of class X at SMAN 2 Seluma.